2015
DOI: 10.5194/hess-19-4113-2015
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall erosivity estimation based on rainfall data collected over a range of temporal resolutions

Abstract: Abstract. Rainfall erosivity is the power of rainfall to cause soil erosion by water. The rainfall erosivity index for a rainfall event (energy-intensity values -EI 30 ) is calculated from the total kinetic energy and maximum 30 min intensity of individual events. However, these data are often unavailable in many areas of the world. The purpose of this study was to develop models based on commonly available rainfall data resolutions, such as daily or monthly totals, to calculate rainfall erosivity. Eleven stat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 30 publications
(33 reference statements)
1
51
0
6
Order By: Relevance
“…High consistency with other studies indicates that the method used in this study (based on daily rainfall series) is reliable. This is further validated by the works Xie et al [47] and Yin et al [48], who calibrated and compared models suitable for estimating erosivity from daily rainfall data. The changing climate could be a strong factor influencing the trends and variability of rainfall erosivity and erosivity density in time and space.…”
Section: Discussionmentioning
confidence: 87%
“…High consistency with other studies indicates that the method used in this study (based on daily rainfall series) is reliable. This is further validated by the works Xie et al [47] and Yin et al [48], who calibrated and compared models suitable for estimating erosivity from daily rainfall data. The changing climate could be a strong factor influencing the trends and variability of rainfall erosivity and erosivity density in time and space.…”
Section: Discussionmentioning
confidence: 87%
“…Analysis from 18 weather stations with 1‐min precipitation data distributed across the central and eastern regions of China (the same data set used by Yin et al, 2015) showed that the behavior of the USLE was very similar to that of the RUSLE2 (the average deviation of the R factor for 18 stations is 0.4%). The RUSLE underestimated R factor values by about 9.3% (Table 2).…”
Section: Development Of the R Factor In New Versions Of The Uslementioning
confidence: 95%
“…However, this kind of precipitation record is typically lacking for yearly global mapping in Asia and Africa. Some alternative methods that used monthly precipitation were applied as substitutes for the lack of 30-min rainfall intensity (Diodato & Bellocchi, 2007;Yin, Xie, Liu, & Nearing, 2015). As we did not intend to precisely estimate the absolute amount of erosion, the basic formula of Fournier index was used as follows (Cerretelli et al, 2018;Fenta et al, 2017;Markose & Jayappa, 2016; Parras-Alcantara, Lozano-Garcia, Keesstra, Cerda, & Brevik, 2016;Wu, Liu, & Ma, 2016).…”
Section: The Estimation Of the Components In Rusle Modelmentioning
confidence: 99%